(untitled) (Journal of Libya for geographical studies, 2026)
Livestock production systems in arid and semi-arid lands are changing due to increasing population pressures, ongoing demands on water and rangelands, and natural factors. This paper examines a transformation process that spanned nearly a century, marked by the transition from nomadic pastoralism to a stable agro-pastoral system in northeastern Morocco. The general aim of the study is to understand the shift toward intensive agro-pastoral production systems in the semi-arid Tafrata Plain within the Guercif Basin, where this transformation is characterized by sedentarization, abandonment of transhumance, and the use of stables for rangeland rehabilitation and fodder production. These changes were accompanied by diversification in fodder crops, with livelihoods increasingly dependent on irrigated agriculture rather than livestock mobility. The results indicate that the observed transformation in the study area is moving toward an unsustainable intensive agro-pastoral system, accompanied by emerging risks such as land-use conflicts due to the weakening of communal property rights.